PEMBELAJARAN BERDIFERENSIASI PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL DI SMP NEGERI 76 JAKARTA - Lidya Rahmawati; Desy Safitri; Sujarwo (STKIP Subang, 2025)
This study was conducted to determine Differentiated Learning in Social Studies Subjects at SMP Negeri 76 Jakarta. The objectives of this study are 1.) To determine how differentiated learning in Social Studies subjects is implemented at SMP Negeri 76 Jakarta. 2.) To determine what are the obstacles in differentiated learning in Social Studies subjects at SMP Negeri 76 Jakarta. Data collection techniques through observation, interviews, and documentation. The subjects of this study consisted of key informants Principal, key informants Vice Principal for Curriculum and Social Studies Teachers, and four students. The results of this study indicate that: 1.) Differentiated learning at SMP Negeri 76 Jakarta is implemented through the planning stage, including teacher training, workshops, MGMP, diagnostic assessments, and the creation of teaching modules. The implementation stage includes differentiation of content, processes, products, and learning environments. The evaluation stage is through supervision and continuous formative assessment. 2.) Obstacles in differentiated learning include time constraints, teacher administrative burdens, and lack of teacher skills.